LEGAL STUDY OF PANGANDARAN KARST LANDSCAPE AREA FOR GEOTOURISM TO REACH SUSTAINABLE DEVELOPMENT GOALS (SDGs) 15 - Reynata Alya Hartono; Nia Kurniati; Dadang Epi Sukarsa (Sosiohumaniora, 2020)
Pangandaran Regency conducts geotourism activities in thiskarst landscape area. This karst landscape needs to be protected by the local government because ecological functions are useful for life and have high scientific value for education. Geotourism in Pangandaran Regency faces constraints due to local regulations that have not been synchronized with the establishment of the karst landscape so there is a need for legal studies to realize sustainable development in this area. The research method used is normative juridical research based on secondary data in the form of primary legal materials and secondary legal materials related to the karst landscape in Pangandaran Regency. The result of the study show that out of sync and out of harmony Regulation of Regional Spatial Regional Regulation of Pangandaran Regency Number 3 of 2018 concerning the Regional Spatial Planning of Pangandaran Regency in 2018-2038 with Ministerial Decree of Energy and Mineral Resources (ESDM) No. 98 K/40/MEM/2019 concerning the Determination of the Pangandaran Karst Landscape Area which will have an impact on the creation of non-optimal use of spatial in accordance with functions of the area. From this study, it can be concluded that the tourism village objects in the karst protected area from the karst function based on the landscape karst area rules are not disturbed must still refer to the principle of environmentally sustainable development that has been regulated by both local and central government.